2009
DOI: 10.1007/978-3-642-04128-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Some Open Questions Related to Cuckoo Hashing

Abstract: Abstract. The purpose of this brief note is to describe recent work in the area of cuckoo hashing, including a clear description of several open problems, with the hope of spurring further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…We review cuckoo hashing and its connection to random hypergraphs; for more background, see [19]. In standard cuckoo hashing [23], keys are placed into a hash table with each bucket containing one item, and each key has two choices of bucket locations determined by random hash values.…”
Section: Cuckoo Hashingmentioning
confidence: 99%
“…We review cuckoo hashing and its connection to random hypergraphs; for more background, see [19]. In standard cuckoo hashing [23], keys are placed into a hash table with each bucket containing one item, and each key has two choices of bucket locations determined by random hash values.…”
Section: Cuckoo Hashingmentioning
confidence: 99%
“…Though cuckoo hashing has been mostly studied as a technique for software hash tables, hardware variants have been proposed to implement lookup tables in IP routers [16]. For additional references, Mitzenmacher has a survey on recent research in cuckoo hashing [32].…”
Section: Related Workmentioning
confidence: 99%
“…Together with (13), this proves (12). It follows from (12) that to finish the proof, all we need to show is that if > 0 is an arbitrary positive constant then we have…”
Section: Proof Of Lemmamentioning
confidence: 56%
“…They showed that given ε , their bounds hold for any d large enough to give the existence of a matching w.h.p. Mitzenmacher gives a survey on Cuckoo Hashing and Problem 1 of the survey asks for the expected insertion time.…”
Section: Introductionmentioning
confidence: 99%